Psychological characteristics of sports performance: Analysis of professional and semiprofessional football referees (2020)
Sports psychology acknowledges the importance of referees in sports. However, evidence is still needed on psychological variables related to refereeing decisions. Psychological characteristics related to sports performance (Stress Control, Influence of Performance Evaluation, Motivation, Mental Skills, and Team Cohesion) were assessed and compared to referee role (referees vs assistant referees), experience, age, and education level. A cross-sectional design was realized, sixty-one professional and semiprofessional referees from Colombia (Mage = 22.5; SD = 4.1) completed the questionnaire for Psychological Characteristics related to Sports Performance adapted for Football Referees (CPRD-AF, for its Spanish acronym). Findings revealed that psychological characteristics are consistent regarding the referee role and experience. Differences were found between stress control and age [FSC (3, 57) =3.83, p =.27, η2 =.38], were the 28-34-year-old group was significantly higher than the 16-21-year-old group. Significant differences were found between stress control and education level [FSC(4, 56) =3.19, p =.030, η2 =.14], postgraduate referees had higher stress control compared with undergraduate referees (p <.027). Performance evaluation has a significantly higher influence on postgraduate referees than college referees (p<.036). Future research needs to evaluate social factor and psychological characteristics related to refereeing performance and include different types of referees role. © JPES.